Classroom discourse: a descriptive study on teachers’ use of English in EFL classrooms - Indriani; Sari, Puspa; Jusriati (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
The use of English in classroom interaction remains a challenge in many EFL contexts, particularly in Indonesia and in this case in Thailand. As the classroom often becomes the primary space for exposure to English, teacher discourse plays a critical role in shaping opportunities for meaningful interaction. This study aims to describe how English is used in classroom discourse and how teachers’ strategies influence student participation. Employing a descriptive qualitative design, the study involved one experienced English teacher from Thailand selected through purposive sampling. Data were collected using an observation checklist and field notes, and then analyzed thematically to identify patterns of English use, code-switching, and discourse practices. The findings indicate that classroom discourse was dominated by giving instructions and code-switching. English use for explaining material and grammar was limited, while questioning occurred regularly. However, corrective feedback, pronunciation practice, authentic material use, and encouragement for students’ active participation were minimal or absent. In conclusion, teacher discourse ensured procedural clarity but reinforced a teacher-centered environment, offering limited communicative opportunities. Pedagogical implications highlight the importance of adopting student-centered approaches, integrating authentic resources, corrective feedback, and motivational strategies to promote learners’ active use of English.